Different lymph node staging systems in patients with gastric cancer from Korean: What is the best prognostic assessment tool?. Issue 25 (June 2016) - Lee, Jin Won; Ali, Bandar; Park, Cho Hyun; Song, Kyo Young
Abstract : Abstract: To investigate whether the log odds of positive lymph nodes (LODDS) system is a more accurate prognostic tool than the number-based (pN) or ratio-based (rN) lymph node staging system in Korean patients with gastric cancer (GC). The LODDS is a recently proposed staging modality in surgical oncology. However, it is unclear whether LODDS is superior to the pN or rN system in terms of predicting the prognosis of GC patients who underwent radical gastrectomy with extended lymphadenectomy and had a greater number of retrieved lymph nodes. Clinicopathological data from 3929 patients who had undergone curative gastrectomy for GC were reviewed. In addition, overall survival rates according to pN and rN classification stratified by the LODDS were analyzed. A multivariate analysis of survival rate was performed using a Cox proportional hazard model. pN, rN, and LODDS were significantly correlated with 5-year survival rate. Spearman correlation test showed no correlation between LODDS and number of lymph nodes retrieved. The receiver operating characteristic (ROC) curves showed that the 3 staging systems had comparable prognostic accuracy ( P  < 0.05). Survival analysis according to pN and rN classification stratified by the LODDS staging system demonstrated that LODDS is superior to pN and rN. The LODDS is independently and significantly associated with the OS of Korean patients with GC, and its prognostic value is superior to that of the other lymph node staging systems in Korean patients.